Pronouns : grammar and representation - Simon, Horst J.; Wiese, Heike (J. Benjamins, 2002)
The contributions of this thematic collection center around the typology of pronominal paradigms, the generation of syntactic and semantic representations for constructions containing pronouns, and the neurological underpinnings for linguistic distinctions that are relevant for the production and interpretation of these constructions. They come from different theoretical approaches and methodological backgrounds and take into account data from a wide range of Indoeuropean and non-Indoeuropean languages. Bringing together a cross-section of recent research on the grammar and representation of p.
Keywords: Grammar, Comparative and general -- Pronoun.; Pronom.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Grammar, Comparative and general -- Pronoun; Voornaamwoorden.; Grammatica.; Grammaire.; Grammaire comparée.; Electronic book.